A method for synthesizing lithium iron phosphate positive electrode material without liquid solvent assistance

Through the liquid solvent-free synthesis method, components A and B with specific properties are used as flow-gase anti-adhesive agents and cooperate with iron phosphate to solve the problems of uncontrollable factors, high energy consumption and poor mixing uniformity in the preparation of lithium iron phosphate positive electrode materials in solid-phase method, achieving a high-efficiency and low-energy consumption production process, and improving material performance.

CN115188934BActive Publication Date: 2025-04-25JIANGSU YOUANSHI BATTERY MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210644684.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-08
Publication Date
2025-04-25
Estimated Expiration
2042-06-08

AI Technical Summary

Technical Problem

The method of preparing lithium iron phosphate positive electrode material in solid phase method has many uncontrollable factors, huge energy consumption, low production efficiency, and poor mixing uniformity of raw materials.

Method used

The liquid solvent-free synthesis method is adopted, and components A and B of specific properties are combined as a gasket anti-adhesive agent, and combined with iron phosphate to perform solid phase depolymerization and solid state mixing, avoiding uncontrollable factors in the solvent removal process and improving the uniformity of raw material mixing.

Benefits of technology

It realizes uniform mixing of raw materials without adding solvents, reduces energy consumption by more than 70%, improves production efficiency, and improves the performance of lithium iron phosphate positive electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003683615610000101
    Figure BDA0003683615610000101
Patent Text Reader

Abstract

The present invention relates to the field of lithium iron phosphate synthesis, and discloses a method for synthesizing lithium iron phosphate positive electrode materials without liquid solvent assistance, comprising the following steps: mixing iron phosphate with a flow-aid anti-adhesive agent, crushing and depolymerizing, and obtaining a depolymerized precursor; the flow-aid anti-adhesive agent comprises component A and component B, component A comprises one or more of graphite, graphite fluoride, molybdenum disulfide, boron nitride and talcum powder, and component B comprises one or more of magnesium stearate, lithium stearate, polyoxymethylene, polyimide, polyparahydroxybenzoic acid and nylon; solid-state mixing of the depolymerized precursor and other raw materials; sintering and crushing. The present invention compounds component A and component B with specific properties as flow-aid anti-adhesive agents, and cooperates with iron phosphate, so as to realize the preparation of lithium iron phosphate positive electrode materials by a solvent-free solid phase method, avoid uncontrollable factors generated in the process of removing solvents, improve the uniformity of raw material mixing, and give lithium ion batteries better performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium iron phosphate synthesis, and in particular to a method for synthesizing lithium iron phosphate positive electrode materials without the assistance of liquid solvents. Background Art

[0002] At present, the main cathode materials for lithium-ion batteries are layered LiMO2 (M = Co, Ni), spinel LiMn2O4, LiNi 0.5 Mn 1.5 O4 and olivine-type LiFePO4. Among them, lithium iron phosphate (LiFePO4) has the advantages of abundant raw material resources, good thermal stability, no pollution to the environment and high safety. It is gradually becoming one of the most promising positive electrode materials for lithium-ion batteries, and plays an important role in my country's energy structure adjustment and the realization of carbon peak and carbon neutrality goals. Correspondingly, the industry's demand for lithium iron phosphate materials is also increasing. It is predicted that the annual demand for lithium iron phosphate will reach more than two million tons in 2025, and it has gradually become a bulk commodity.

[0003] The synthesis methods of lithium iron phosphate are usually divided into two types: solid phase method and liquid phase method. The liquid phase method includes hydrothermal method, coprecipitation method and sol-gel method, etc. The obtained lithium iron phosphate has uniform phase and small particle size, but has high requirements for reaction conditions. Improper control of reaction conditions will directly affect the performance of lithium iron phosphate, causing its phase and particle size to be uneven, and will also cause safety hazards such as boiling. The solid phase method uses lithium source (such as lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate, lithium dihydrogen phosphate, etc.), iron source (such as ferrous oxalate, ammonium ferrous phosphate, ferrous phosphate, ferrous oxide, etc.), phosphorus source (such as ammonium ferrous phosphate, ferric phosphate, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, lithium phosphate, etc.) and carbon source (such as glucose, sucrose, etc.) as raw materials, after ball milling and mixing, lithium iron phosphate is formed by sintering. Compared with the liquid phase method, the reaction conditions of the solid phase method are easy to control, and the production process is simple and safe. However, there is a problem that the raw materials are difficult to mix evenly, which will cause insufficient and uneven reactions, resulting in poor uniformity of the obtained lithium iron phosphate positive electrode material, which will have an adverse effect on the performance of lithium-ion batteries.

[0004] In order to improve the uniformity of raw material mixing, the use of solvents cannot be avoided in the process of preparing lithium iron phosphate by solid phase method. For example, patent CN113929070B discloses a method for preparing high-rate lithium iron phosphate positive electrode materials. First, the iron source and lithium source are weighed according to the molar ratio of 1:1 to 1:1.05, and then 5-15% of the carbon source and 0-1% of the metal ion dopant of the total mass of the iron source and lithium source are weighed, and water ball milling and sand milling are added. The sand milling D50 is controlled at 100-200nm, and then the precursor is sprayed. The precursor is put into the sintering furnace, and nitrogen protection is introduced at the same time. The temperature during sintering is 650-700℃. After cooling, the sintered material is obtained, and then the sintered material is crushed, sieved and iron removed to obtain lithium iron phosphate. This patent can improve the uniformity of raw material mixing to a certain extent by adding water ball milling, but it is necessary to remove water by spray drying later. There are many uncontrollable factors in this process, and the entire production process consumes huge energy and has low production efficiency. Summary of the invention

[0005] In order to solve the problem that there are many uncontrollable factors in the method of preparing lithium iron phosphate by solid phase method, and the whole production process has huge energy consumption and low production efficiency, the present invention provides a method for synthesizing lithium iron phosphate positive electrode materials without liquid solvent assistance. The present invention can realize the preparation of lithium iron phosphate positive electrode materials by solvent-free solid phase method by compounding component A and component B with specific properties as flow-aiding anti-adhesive agents, and matching them with a specific iron source (iron phosphate), avoiding the uncontrollable factors generated in the process of removing solvents, high pollution, and low production efficiency problems, while avoiding agglomeration and caking during the mixing process, improving the uniformity of raw material mixing, and giving lithium ion batteries better performance.

[0006] The specific technical scheme of the present invention is:

[0007] First, the present invention provides a method for synthesizing lithium iron phosphate positive electrode materials without liquid solvent assistance, comprising the following steps:

[0008] (1) solid phase depolymerization: mixing ferric phosphate with a flow aid and anti-adhesive agent, crushing and depolymerizing, and obtaining a depolymerized precursor with a particle size of 0.2 to 2 μm; the flow aid and anti-adhesive agent comprises component A and component B; the component A comprises one or more of graphite, graphite fluoride, molybdenum disulfide, boron nitride and talc; the component B comprises one or more of magnesium stearate, lithium stearate, polyoxymethylene, polyimide, polyparahydroxybenzoic acid and nylon;

[0009] (2) solid-state mixing: solid-state mixing the depolymerized precursor obtained in step (1) with other raw materials, wherein the other raw materials include a lithium source and a carbon source, to obtain a mixed material;

[0010] (3) Sintering and pulverizing: The mixed material obtained in step (2) is placed in an inert gas atmosphere for sintering, and then pulverized to obtain a lithium iron phosphate positive electrode material.

[0011] In the present invention, by compounding component A and component B with specific properties as flow-aiding and anti-adhesive agents and coordinating them with a specific iron source (iron phosphate), the crushing and depolymerization of the iron source can be promoted, the uniformity of raw material mixing can be improved, and the prepared lithium iron phosphate can be made more uniform. The specific mechanism is as follows:

[0012] 1) Component A can reduce the friction between iron phosphate particles through physical lubrication, such as slippage between layers, thereby preventing them from agglomerating; Component B can form coordination bonds with the dangling bonds in iron phosphate and attach to the surface of component A, using component A as an anchor point to promote the depolymerization of iron phosphate and prevent it from agglomerating. In this way, after component A and component B are compounded, a synergistic effect of "1+1>2" can be produced, which helps to improve the crushing and depolymerization effect of iron phosphate.

[0013] 2) The present invention selects iron phosphate among all iron sources in order to improve the fragmentation and depolymerization effect of the precursor. On the one hand, in iron phosphate, phosphate has more dangling bonds, which can form coordination bonds with component B in the flow-aiding anti-adhesive agent, thereby promoting fragmentation and depolymerization. On the other hand, although some other iron sources (such as ferrous phosphate and ammonium ferrous phosphate) also contain phosphate, the effect is not as good as that of iron phosphate. The reason is that: in the process of synthesizing iron phosphate, iron hydroxide will be generated when the pH exceeds 4, so it is necessary to add excess phosphoric acid to control the pH below 4 (usually 3-4), while in the process of synthesizing ferrous phosphate and ammonium ferrous phosphate, no by-products will be generated when the pH is high, and the reaction is incomplete when the pH is less than 7, so the pH is usually controlled at 8-9. Therefore, the commercially available iron phosphate usually has an excess of phosphate of about 2-4%. When it is used as an iron source to synthesize lithium iron phosphate, it can form more coordination bonds with component B in the flow-aiding anti-adhesive agent, which is beneficial to the fragmentation and depolymerization of the iron source.

[0014] Through the above manner, in the process of solid-phase synthesis of lithium iron phosphate, the present invention can achieve uniform mixing of raw materials without adding solvent (the effect is equivalent to the method of adding solvent), so there is no need to remove the solvent by spray drying or the like, which can reduce energy consumption by more than 70%, and the energy-saving and emission-reduction effect is amazing; and, compared with the method of adding solvent, the method of the present invention can improve the uniformity and conductivity of the carbon coating layer on the surface of lithium iron phosphate to a greater extent through chemical adsorption and in-situ carbonization of the carbon-containing ligand (component B), thereby improving the material performance.

[0015] Preferably, the mass ratio of component A to component B is (0.5-2):1.

[0016] Preferably, in step (1), the mass ratio of the ferric phosphate to the flow-aiding and anti-adhesive agent is 1:(0.01-0.05).

[0017] Preferably, in step (1), the crushing and deagglomeration is carried out by a combination of one or more of a powder deagglomerator, a stirring ball mill, a drum ball mill, a jet mill, a vibration mill, a vortex mill, a Raymond mill, an inclined ball mill and a pendulum mill.

[0018] Preferably, in step (1), the time for crushing and depolymerizing is 0.5 to 12 hours.

[0019] Preferably, in step (2), the mass ratio of the depolymerized precursor, the lithium source and the carbon source is 1:(0.2-0.3):(0.05-0.15).

[0020] Preferably, in step (2), the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium oxalate.

[0021] Preferably, in step (2), the carbon source comprises one or more of glucose, sucrose, citric acid, carbon black, graphene and carbon nanotubes.

[0022] Preferably, in step (2), the other raw materials also include doping substances; the doping substances include one or more of a magnesium source, an aluminum source, a titanium source, a zirconium source, a manganese source and a niobium source; and the mass ratio of the depolymerized precursor to the doping substance is 1:(0.002-0.08).

[0023] Preferably, in step (2), the solid-state mixing is carried out by a combination of one or more of a high-speed mixer, a three-dimensional mixer, a planetary ball mill, a stirring ball mill, a drum ball mill, a vibration mill, a Raymond mill, an oblique ball mill and a pendulum mill; and the solid-state mixing time is 0.5 to 48 hours.

[0024] Preferably, in step (3), the sintering temperature is 500-900° C. and the sintering time is 2-20 hours.

[0025] Furthermore, in step (1), component B includes one or more of polyoxymethylene, polyimide, polyparahydroxybenzoic acid and nylon; in step (2), the carbon source includes one or more of glucose, sucrose and citric acid; in step (3), the specific process of sintering includes the following steps: first roasting at 200-300°C for 60-120 min, then heating to 350-450°C for roasting for 60-120 min, and then heating to 550-900°C and keeping warm for 2-20 h.

[0026] In the first stage, when calcined at 200-300°C, the carbon source (glucose, sucrose or citric acid) is carbonized, and component B (polyoxymethylene, polyimide, polyparahydroxybenzoic acid or nylon) is basically not carbonized; in the second stage, when calcined at 350-450°C, the carbon source is completely carbonized, and component B begins to carbonize. The present invention sets the above two carbonization stages according to the different carbonization decomposition temperatures of component B and the carbon source, which can make the carbonization speed more stable and better controllable, and is conducive to obtaining a lithium iron phosphate positive electrode material with better performance.

[0027] Preferably, in step (3), the pulverization is carried out by one or a combination of a planetary ball mill, a stirring ball mill, a drum ball mill, a vibration mill, a Raymond mill, an oblique ball mill and a pendulum mill.

[0028] Preferably, in step (3), the inert gas is nitrogen and / or argon.

[0029] Preferably, in step (1), component A comprises modified graphite; the modified graphite is graphite with anion-modified polydopamine grafted on the surface and between the layers.

[0030] When graphite is used as a flow-aiding and anti-adhesive agent, it can not only promote the depolymerization of the raw materials, but also serve as a conductive agent to improve the conductivity of the lithium iron phosphate positive electrode material. Although the flow-aiding and anti-adhesive and conductive effects can be improved by increasing the amount of graphite used, it will also cause the content of active substances in the positive electrode to decrease, which is not conducive to the improvement of battery performance. In order to improve battery performance and meet the needs of some fields for high-performance batteries, the present invention modifies graphite by grafting anion-modified polydopamine on its surface and interlayers. It can improve the flow-aiding and anti-adhesive effect and conductivity of graphite without reducing the content of active substances in the positive electrode, thereby improving battery performance to a large extent. The specific mechanism is as follows:

[0031] 1) The graphite sheets have good conductivity inside, but the sheets are bonded by van der Waals forces, and the conductivity is poor. In the process of sintering to form lithium iron phosphate, the polydopamine between the graphite sheets is carbonized to form a porous carbon material, which can form a bridge between the sheets to form a conductive channel, thereby improving the conductivity of the graphite. In addition, the porous carbon material formed by the carbonization of polydopamine is doped with pyrrole-type nitrogen and pyridinic nitrogen, which can give the carbon material better conductivity.

[0032] 2) During the process of crushing and depolymerization, the polydopamine on the graphite surface can enhance the adsorption of graphite on the surface of iron phosphate, which is beneficial for the graphite to play a flow-aiding and anti-adhesive role.

[0033] 3) While polydopamine between graphite sheets improves the conductivity of graphite, the entanglement between its molecular chains also hinders the slippage between graphite sheets, resulting in poor effect of polydopamine in improving the flow-aiding and anti-adhesive effect of graphite. The present invention uses anion-modified polydopamine and utilizes electrostatic repulsion to reduce the entanglement between polydopamine molecular chains, thereby reducing the influence of interlayer polydopamine on the flow-aiding and anti-adhesive effect of graphite.

[0034] Preferably, the method for preparing the modified graphite comprises the following steps:

[0035] (1.1) In an anaerobic atmosphere, dopamine hydrochloride is dissolved in Tris-HCl buffer, and graphite is added thereto for full immersion; the anaerobic atmosphere is replaced with an aerobic atmosphere for polymerization reaction; after the reaction is completed, the product is separated to obtain polydopamine-modified graphite;

[0036] (1.2) Taurine is dissolved in Tris-HCl buffer, polydopamine-modified graphite is added thereto, potassium hydroxide is added to adjust the pH to 8.0-9.0, and after being evenly dispersed, a Schiff base reaction is carried out; after the reaction is completed, the product is separated and dried to obtain modified graphite.

[0037] In step (1.1), in an oxygen-free atmosphere, dopamine does not polymerize and easily enters between graphite sheets, thereby improving the conductivity of graphite. Then, in an aerobic atmosphere, dopamine can undergo oxidation, intramolecular rearrangement, and self-polymerization, thereby forming dopamine on the graphite surface and interlayer grafts.

[0038] In step (1.2), the amino group in taurine reacts with polydopamine to undergo a Schiff base reaction, so that the sulfonic acid group can be grafted onto the polydopamine. By adding potassium hydroxide, on the one hand, the sulfonic acid group can be made negatively charged, thereby reducing the entanglement between the polydopamine molecular chains; on the other hand, during the drying process, potassium hydroxide precipitates and is doped in the polydopamine, which can play an etching role during sintering, so that the carbon material formed by the carbonization of polydopamine has a porous structure, which is conducive to the diffusion of the electrolyte. At the same time, it can also avoid the significant reduction in the volume of the interlayer polydopamine after carbonization, ensuring that it can play a good bridging role and improve the conductivity of graphite.

[0039] Second, the present invention provides a lithium iron phosphate positive electrode material prepared by the method.

[0040] Third, the present invention provides the application of the lithium iron phosphate positive electrode material in lithium ion batteries.

[0041] Compared with the prior art, the present invention has the following advantages:

[0042] (1) By compounding component A and component B with specific properties as flow aids and anti-adhesive agents, and coordinating them with a specific iron source (iron phosphate), it is possible to realize the solvent-free solid phase method for preparing lithium iron phosphate positive electrode materials, avoiding the uncontrollable factors generated in the process of removing the solvent, as well as the problems of high energy consumption, high pollution and low production efficiency, and solving the problems of agglomeration, caking and agglomeration of all-solid raw materials in the mixing process, thereby improving the uniformity of raw material mixing and giving the battery better performance; (2) By utilizing the chemical adsorption and in-situ carbonization of the carbon-containing coordination agent (component B), the uniformity and conductivity of the carbon coating layer on the surface of lithium iron phosphate can be improved to a greater extent, thereby reducing the internal resistance of the battery;

[0043] (3) According to the different carbonization decomposition temperatures of component B and the carbon source, two carbonization stages are set, which can make the carbonization rate more stable and better controllable, and is conducive to obtaining lithium iron phosphate positive electrode materials with better performance. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with the embodiments.

[0045] Overall embodiment

[0046] A method for synthesizing a lithium iron phosphate positive electrode material without the assistance of a liquid solvent comprises the following steps:

[0047] (1) solid phase depolymerization: mixing iron phosphate with a flow aid and anti-adhesive agent, wherein the mass ratio of the iron phosphate to the flow aid and anti-adhesive agent is 1:(0.01-0.05), and performing crushing and depolymerization for 0.5-12 hours to obtain a depolymerized precursor with a particle size of 0.2-2 μm;

[0048] The flow-aiding and anti-adhesive agent comprises component A and component B in a mass ratio of (0.5-2):1; the component A comprises one or more of graphite, graphite fluoride, molybdenum disulfide, boron nitride and talc; the component B comprises one or more of magnesium stearate, lithium stearate, polyoxymethylene, polyimide, polyparahydroxybenzoic acid and nylon;

[0049] The crushing and deagglomeration is carried out by combining one or more of a powder deagglomeration machine, a stirring ball mill, a drum ball mill, a jet mill, a vibration mill, a vortex ring mill, a Raymond mill, an inclined ball mill and a pendulum mill;

[0050] (2) solid-state mixing: solid-state mixing the depolymerized precursor, lithium source, carbon source and doping material in a mass ratio of 1: (0.2-0.3): (0.05-0.15): (0.002-0.08) for 0.1-48 hours to obtain a mixture;

[0051] The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium oxalate;

[0052] The carbon source includes one or more of glucose, sucrose, citric acid, carbon black, graphene and carbon nanotubes;

[0053] The doping material includes one or more of a magnesium source, an aluminum source, a titanium source, a zirconium source, a manganese source and a niobium source;

[0054] The solid-state mixing is carried out by one or more of a high-speed mixer, a three-dimensional mixer, a planetary ball mill, a stirring ball mill, a drum ball mill, a vibration mill, a Raymond mill, an oblique ball mill and a pendulum mill;

[0055] (3) Sintering and pulverizing: placing the mixture in an inert gas atmosphere, sintering at 500-900° C. for 2-20 h, and then pulverizing to obtain a lithium iron phosphate positive electrode material;

[0056] The inert gas is nitrogen and / or argon;

[0057] The pulverizing is carried out by one or a combination of a planetary ball mill, a stirring ball mill, a drum ball mill, a vibration mill, a Raymond mill, an inclined ball mill and a pendulum mill.

[0058] A lithium ion battery using the lithium iron phosphate positive electrode material.

[0059] Optionally, in step (1), the component A comprises modified graphite; and the method for preparing the modified graphite comprises the following steps:

[0060] (1.1) In an anaerobic atmosphere, dopamine hydrochloride is dissolved in a Tris-HCl buffer solution with a pH of 7.5 to 8.0, and graphite is added thereto, wherein the mass volume ratio of dopamine hydrochloride, graphite and Tris-HCl buffer solution is 1 g: (0.5 to 1) g: (80 to 100) mL, and ultrasonic immersion is performed for 1 to 2 hours; the anaerobic atmosphere is replaced with an aerobic atmosphere, and the reaction is stirred at 50 to 60° C. for 4 to 6 hours; after the reaction is completed, the product is separated to obtain polydopamine-modified graphite;

[0061] (1.2) Taurine is dissolved in Tris-HCl buffer, and polydopamine-modified graphite is added thereto, wherein the mass volume ratio of taurine, polydopamine-modified graphite and Tris-HCl buffer is 1 g: (0.2-0.5) g: (40-60) mL, potassium hydroxide is added to adjust the pH to 8.0-9.0, and after being evenly dispersed, the mixture is stirred and reacted at 55-65° C. for 5-8 hours; after the reaction is completed, the product is separated and dried to obtain modified graphite.

[0062] Optionally, in step (1), component B includes one or more of polyoxymethylene, polyimide, polyparahydroxybenzoic acid and nylon; in step (2), the carbon source includes one or more of glucose, sucrose and citric acid; in step (3), the specific process of sintering includes the following steps: first roasting at 200-300°C for 60-120 min, then heating to 350-450°C for roasting for 60-120 min, and then heating to 550-900°C and keeping warm for 2-20 h.

[0063] Example 1

[0064] The lithium iron phosphate positive electrode material is prepared by the following steps:

[0065] (1) Solid phase depolymerization: Anhydrous iron phosphate, graphite and magnesium stearate in a mass ratio of 1:0.01:0.02 were added into a stirred ball mill and ball milled at a speed of 500 rpm for 9 h to obtain a precursor with a particle size of 0.5-0.8 μm;

[0066] (2) Solid-state mixing: lithium carbonate, glucose and magnesium carbonate with masses of 0.2 times, 0.1 times and 0.01 times the mass of the precursor, respectively, were weighed and put into a stirred ball mill containing the precursor, and ball milled at a speed of 300 rpm for 24 h to obtain a mixed material;

[0067] (3) Sintering: The mixed material is placed in a tubular furnace, the air in the furnace is replaced with nitrogen, and then the temperature is raised to 700°C, kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain a sintered material;

[0068] (4) Crushing: The sintered material was transferred to a stirring ball mill, ball-milled at a rotation speed of 300 rpm for 5 h, sieved, and packaged to obtain a lithium iron phosphate positive electrode material.

[0069] Example 2

[0070] The lithium iron phosphate positive electrode material is prepared by the following steps:

[0071] (1) Solid phase depolymerization: Anhydrous iron phosphate, graphite and nylon in a mass ratio of 1:0.02:0.02 were added into a stirred ball mill and ball milled at a speed of 600 rpm for 5 h to obtain a precursor with a particle size of 0.9 to 1.5 μm;

[0072] (2) Solid-state mixing: lithium carbonate, glucose, carbon black and aluminum hydroxide with masses of 0.3, 0.05, 0.05 and 0.02 times the mass of the precursor, respectively, were put into a stirred ball mill containing the precursor and ball-milled at a speed of 400 rpm for 12 h to obtain a mixture;

[0073] (3) Sintering: The mixed material is placed in a tubular furnace, the air in the furnace is replaced with nitrogen, and then the temperature is raised to 800°C, kept at this temperature for 20 hours, and naturally cooled to room temperature to obtain a sintered material;

[0074] (4) Crushing: The sintered material was transferred to a stirring ball mill, ball-milled at a rotation speed of 400 rpm for 5 h, sieved, and packaged to obtain a lithium iron phosphate positive electrode material.

[0075] Example 3

[0076] The lithium iron phosphate positive electrode material is prepared by the following steps:

[0077] (1) Solid phase depolymerization: Anhydrous iron phosphate, graphite and polyimide in a mass ratio of 1:0.03:0.02 were added into a stirred ball mill and ball milled at a speed of 500 rpm for 12 h to obtain a precursor with a particle size of 1.6 to 2 μm;

[0078] (2) Solid-state mixing: lithium carbonate, glucose, carbon black and manganese oxalate with masses of 0.25 times, 0.1 times, 0.01 times and 0.05 times the mass of the precursor, respectively, were put into a stirred ball mill containing the precursor, and ball milled at a speed of 400 rpm for 48 h to obtain a mixture;

[0079] (3) Sintering: The mixed material is placed in a tubular furnace, the air in the furnace is replaced with nitrogen, and then the temperature is raised to 900°C, kept at this temperature for 2 hours, and naturally cooled to room temperature to obtain a sintered material;

[0080] (4) Crushing: The sintered material was transferred to a stirring ball mill, ball-milled at a rotation speed of 300 rpm for 5 h, sieved, and packaged to obtain a lithium iron phosphate positive electrode material.

[0081] Example 4

[0082] The only difference between this embodiment and embodiment 2 is that step (3) is replaced by: placing the mixture in a tubular furnace, replacing the air in the furnace with nitrogen, and then heating it to 300°C and roasting it for 1.5 hours, then heating it to 450°C and roasting it for 2 hours, and finally heating it to 800°C and keeping it warm for 16.5 hours.

[0083] Example 5

[0084] The difference between this embodiment and embodiment 1 is that in step (1), graphite is replaced with modified graphite of equal mass; the modified graphite is prepared by the following steps:

[0085] (1.1) Replace the air in the reactor with nitrogen, add dopamine hydrochloride and Tris-HCl buffer (pH 8.0, concentration of tris(hydroxymethyl)aminomethane 0.05 mol / L) in a mass-volume ratio of 1 g:100 mL, and after dissolution, add graphite with a mass of 0.5 times that of dopamine hydrochloride, and ultrasonically immerse for 1 hour; replace the nitrogen in the reactor with air, heat to 60°C, and stir at constant temperature for 5 hours; centrifuge and wash to obtain polydopamine-modified graphite;

[0086] (1.2) Taurine and Tris-HCl buffer (pH 8.0, concentration of tris(hydroxymethyl)aminomethane 0.05 mol / L) in a mass-to-volume ratio of 1 g:50 mL were added to a reaction kettle. After dissolution, polydopamine-modified graphite in an amount 0.5 times the mass of taurine was added, and potassium hydroxide was added to adjust the pH to 9.0. After ultrasonic dispersion for 30 min, the temperature was raised to 60°C and stirred at a constant temperature for 8 h. The mixture was centrifuged, washed, and dried to obtain modified graphite.

[0087] Example 6

[0088] The difference between this embodiment and embodiment 1 is that the modified graphite is prepared by the following steps:

[0089] (1.1) Replace the air in the reactor with nitrogen, add dopamine hydrochloride and Tris-HCl buffer (pH 7.5, concentration of tris(hydroxymethyl)aminomethane 0.05 mol / L) in a mass-volume ratio of 1 g:80 mL, and after dissolution, add graphite with a mass of 1 times that of dopamine hydrochloride, and ultrasonically immerse for 2 h; replace the nitrogen in the reactor with air, heat to 50°C, and stir at a constant temperature for 6 h; centrifuge and wash to obtain polydopamine-modified graphite;

[0090] (1.2) Taurine and Tris-HCl buffer (pH 7.5, concentration of tris(hydroxymethyl)aminomethane 0.05 mol / L) in a mass-to-volume ratio of 1 g:40 mL were added to a reaction kettle. After dissolution, polydopamine-modified graphite in an amount 0.2 times the mass of taurine was added, and potassium hydroxide was added to adjust the pH to 8.5. After ultrasonic dispersion for 30 min, the temperature was raised to 55°C and stirred at a constant temperature for 8 h. The mixture was centrifuged, washed, and dried to obtain modified graphite.

[0091] Example 7

[0092] The difference between this embodiment and embodiment 1 is that the modified graphite is prepared by the following steps:

[0093] (1.1) Replace the air in the reactor with nitrogen, add dopamine hydrochloride and Tris-HCl buffer (pH 8.0, concentration of tris(hydroxymethyl)aminomethane 0.05 mol / L) in a mass-to-volume ratio of 1 g:90 mL, and after dissolution, add graphite with a mass of 1 times that of dopamine hydrochloride, and ultrasonically immerse for 1 hour; replace the nitrogen in the reactor with air, heat to 55°C, and stir at constant temperature for 4 hours; centrifuge and wash to obtain polydopamine-modified graphite;

[0094] (1.2) Taurine and Tris-HCl buffer (pH 8.0, concentration of tris(hydroxymethyl)aminomethane 0.05 mol / L) in a mass-to-volume ratio of 1 g:60 mL were added to a reaction kettle. After dissolution, polydopamine-modified graphite in an amount 0.3 times the mass of taurine was added, and potassium hydroxide was added to adjust the pH to 8.0. After ultrasonic dispersion for 30 min, the temperature was raised to 65°C and stirred at a constant temperature for 5 h. The mixture was centrifuged, washed, and dried to obtain modified graphite.

[0095] Comparative Example 1

[0096] The only difference between this comparative example and Example 1 is that in step (1), no graphite and magnesium stearate are added.

[0097] Comparative Example 2

[0098] The difference between this comparative example and Example 1 is that in step (1), graphite and magnesium stearate are replaced with deionized water having a mass content of 21.2% iron phosphate, and after ball milling, spray drying is performed to obtain a precursor.

[0099] Comparative Example 3

[0100] The difference between this comparative example and Example 1 is that in step (1), anhydrous ferric phosphate is replaced with anhydrous ferrous phosphate of equal mass; and in step (2), glucose is not added (minus the carbon source used to reduce the ferric phosphate).

[0101] Comparative Example 4

[0102] The difference between this comparative example and Example 1 is only that, in step (1), magnesium stearate is replaced with graphite of equal mass.

[0103] Comparative Example 5

[0104] The difference between this comparative example and Example 1 is only that, in step (1), graphite is replaced with an equal mass of magnesium stearate.

[0105] Comparative Example 6

[0106] The only difference between this comparative example and Example 5 is that step (1.2) is not performed; the polydopamine-modified graphite obtained in step (1.1) is dried to obtain modified graphite.

[0107] Comparative Example 7

[0108] The difference between this comparative example and Example 5 is that step (1.1) is replaced by: adding dopamine hydrochloride and Tris-HCl buffer (pH 8.0, concentration of tris(hydroxymethyl)aminomethane is 0.05 mol / L) in a mass volume ratio of 1 g:100 mL to the reactor, and after dissolution, adding graphite with a mass of 0.5 times that of dopamine hydrochloride, heating to 60°C, and stirring at a constant temperature for 5 h; centrifuging, washing, and obtaining polydopamine-modified graphite.

[0109] Test Case

[0110] The lithium iron phosphate positive electrode material prepared in Examples 1 to 5 and Comparative Examples 1 to 7 was mixed with PVDF and N-methylpyrrolidone, and the mass ratio of the lithium iron phosphate positive electrode material to PVDF was controlled to be 20:1 to prepare a positive electrode slurry with a solid content of 50wt%; the positive electrode slurry was then coated on an aluminum foil, dried, and pressed to obtain a positive electrode sheet; ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1, and LiPF6 was added to make its concentration 1.0 mol / L to obtain an electrolyte; according to a conventional method, the positive electrode sheet, the graphite negative electrode sheet, the PP separator and the electrolyte were made into a soft-pack lithium-ion battery.

[0111] The soft-pack lithium-ion battery was subjected to performance testing to detect the gram capacity, initial efficiency and internal resistance of its lithium iron phosphate positive electrode material. The results are shown in Table 1.

[0112] Table 1

[0113]

[0114] From Table 1 we can see that:

[0115] (1) Compared with Comparative Example 1, the gram capacity and first charge efficiency of Examples 1 to 3 are significantly higher, which are equivalent to Comparative Example 2; and compared with Comparative Examples 1 and 2, the internal resistance of Example 1 is significantly smaller. This indicates that in the process of crushing and depolymerizing ferrous phosphate, adding a flow-aiding and anti-adhesive agent helps to crush and depolymerize, thereby improving battery performance; and, compared with the method of using water in the prior art, the method of using a flow-aiding and anti-adhesive agent in the present invention can achieve the same effect of improving the gram capacity and first charge efficiency of the battery as water, and does not require spray drying, which can reduce energy consumption, improve production efficiency, and effectively reduce the internal resistance of the battery.

[0116] (2) Compared with Comparative Example 3, the gram capacity and first charge efficiency of Example 1 are significantly higher, and the internal resistance is significantly smaller. It shows that compared with ferrous phosphate, the selection of ferric phosphate as the iron source can make the prepared lithium iron phosphate positive electrode material have better performance. This is because: an excess of phosphoric acid needs to be added to ferric phosphate during the synthesis process, so the commercially available iron phosphate usually contains an excess of phosphate. When it is used as an iron source to synthesize lithium iron phosphate, the dangling bonds in the phosphate can form more coordination bonds between the iron source and component B in the flow-aiding anti-adhesive agent, which is beneficial to the crushing and depolymerization of the iron source, making the raw materials more evenly mixed.

[0117] (3) Compared with Comparative Examples 4 and 5, the gram capacity and first-charge efficiency of Example 1 are significantly higher, and the internal resistance is significantly smaller. This shows that when component A (graphite) and component B (magnesium stearate) are compounded as flow-aiding and anti-adhesive agents, a synergistic effect of "1+1>2" can be produced between the two, promoting the crushing and deagglomeration of iron phosphate. This is because: component A can reduce the friction between iron phosphate particles through physical lubrication, such as slip between lamellae, thereby preventing them from agglomerating; component B can form coordination bonds with dangling bonds in iron phosphate and adhere to the surface of component A, using component A as an anchor point to promote the deagglomeration of iron phosphate and prevent its agglomeration.

[0118] (4) Compared with Example 2, the internal resistance of Example 4 is significantly smaller. This is because: Example 4 adopts a staged calcination method, and sets two carbonization stages according to the different carbonization decomposition temperatures of component B (nylon) and carbon source (glucose), which can make the carbonization speed more stable and more controllable, which is conducive to obtaining a lithium iron phosphate positive electrode material with better performance.

[0119] (5) Compared with Example 1, Example 5 has a significantly higher gram capacity and a significantly lower internal resistance. This is because: Example 5 grafts anion-modified polydopamine on the surface and interlayer of graphite. The surface polydopamine can enhance the adsorption of graphite on the surface of iron phosphate and / or ammonium ferrous phosphate, which is beneficial for the graphite to play a flow-aiding and anti-adhesive role. The interlayer polydopamine forms a porous carbon material after carbonization, which can form a bridge between the sheets to form a conductive channel, thereby improving the conductivity of the graphite.

[0120] (6) Compared with Comparative Example 6, Example 5 has a significantly higher gram capacity and a significantly lower internal resistance. This is because: Example 5 grafts taurine onto polydopamine, which can introduce more negative charges onto the polydopamine molecular chain, thereby utilizing electrostatic repulsion to reduce the entanglement between molecular chains and avoid excessive influence of interlayer polydopamine on the flow-aiding and anti-adhesive effect of graphite.

[0121] (6) Compared with Comparative Example 7, Example 5 has a significantly higher gram capacity and a significantly lower internal resistance. This is because: in the process of grafting polydopamine, Example 5 is first immersed in an oxygen-free atmosphere before polymerization. At this time, dopamine has not yet been polymerized and can easily enter between graphite sheets, thereby grafting more polydopamine between graphite layers. After carbonization, conductive channels are formed between the sheets, thereby improving the conductivity of graphite.

[0122] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0123] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for synthesizing lithium iron phosphate positive electrode materials without liquid solvent assistance, characterized in that: The following steps are involved: (1) Solid phase depolymerization: mixing ferric phosphate with a flow aid and anti-adhesive agent, crushing and depolymerizing, and obtaining a depolymerized precursor with a particle size of 0.2 to 2 μm; the flow aid and anti-adhesive agent comprises component A and component B; the component A comprises one or more of graphite, graphite fluoride, molybdenum disulfide, boron nitride and talc; the component B comprises one or more of magnesium stearate, lithium stearate, polyoxymethylene, polyimide, polyparahydroxybenzoic acid and nylon; (2) solid-state mixing: solid-state mixing the depolymerized precursor obtained in step (1) with other raw materials, wherein the other raw materials include a lithium source and a carbon source, to obtain a mixed material; (3) Sintering and pulverizing: The mixture obtained in step (2) is placed in an inert gas atmosphere for sintering, and then pulverized to obtain a lithium iron phosphate positive electrode material.

2. The method according to claim 1, characterized in that In step (1), the mass ratio of component A to component B is (0.5-2):

1.

3. The method according to claim 1 or 2, characterized in that In step (1), the mass ratio of the ferric phosphate to the flow-aiding and anti-adhesive agent is 1:(0.01-0.05).

4. The method according to claim 1, characterized in that In step (1), the crushing and deagglomeration is carried out by one or more of a powder deagglomeration machine, a stirring ball mill, a drum ball mill, a jet mill, a vibration mill, a vortex ring mill, a Raymond mill, an inclined ball mill and a pendulum mill.

5. The method according to claim 1 or 4, characterized in that In step (1), the time for crushing and depolymerization is 0.5 to 12 hours.

6. The method according to claim 1, characterized in that In step (2), the other raw materials also include doping substances; the doping substances include one or more of a magnesium source, an aluminum source, a titanium source, a zirconium source, a manganese source and a niobium source; and the mass ratio of the depolymerized precursor to the doping substance is 1:(0.002-0.08).

7. The method according to claim 1, characterized in that In step (3), the sintering temperature is 500-900°C and the sintering time is 2-20 hours.

8. The method according to claim 7, characterized in that In step (1), the component B includes one or more of polyoxymethylene, polyimide, polyparahydroxybenzoic acid and nylon; in step (2), the carbon source includes one or more of glucose, sucrose and citric acid; in step (3), the specific process of sintering includes the following steps: first roasting at 200-300°C for 60-120 min, then heating to 350-450°C for roasting for 60-120 min, and then heating to 550-900°C and keeping warm for 2-20 h.

9. A lithium iron phosphate positive electrode material prepared by the method as claimed in any one of claims 1 to 8.

10. Use of the lithium iron phosphate positive electrode material as claimed in claim 9 in a lithium ion battery.

Citation Information

Patent Citations

  • A method for preparing high-rate lithium iron phosphate cathode material

    CN113929070B

  • Hypervolume lithium ion battery positive electrode material, and preparation method and application thereof

    CN105789596A

  • Power lithium ion battery silicon-carbon composite negative electrode material preparation method

    CN106207142A